THE IMPACT OF STAFFING AND COMPENSATION TOWARD EMPLOYEEâS COMPETENSE AT âKONVEKSIâ UNIT OF PRIMKOPAD BEKANGDAM III/SLW - Irawan, Andri; Rosmalia, Lia (Jurnal Manajemen dan Keuangan, 2010)
The objective of this research was to know how far the impact of staffing and compensation toward employeeâs competence and its implication toward employeeâs working method at â konveksiâ unit of Primkopad Bekangdam III/ SLW. The writer here used Path- Analysis to Analyze the data.Based on the data processing toward the first structure by using path- analysis, it was found that staffing had a partial and significant impact of 51,6 % while compensation had impartial and insignificant impact of only 13,9 %. It was caused by the powerful competition between staffing and compensation although both of them had a simultaneous impact of 32,5 %.Keyword: Staffing, compensation, and competence